Artificial Intelligence-Integrated Series Active Filters for Improved Power Quality in EV Infrastructure - Muhammad Hammad u Salam*; Shujaat Ali Rathore; Dr. Nasrullah; Muhammad Irfan; Tahir Abbas; Jamshaid Iqbal Janjua (Spectrum of Engineering Sciences, 2024)
The proliferation of electric vehicles (EVs) increases pressure on power distribution systems. The power demand from EV chargers creates new non-linear loads which deteriorate power quality through harmonic distortions, voltage sags, and voltage swells. This paper proposes the use of Artificial Intelligence (AI) for mitigating power quality problems in active series filters designed for electric vehicle (EV) infrastructure. The AI-assisted hybrid series active filter is supposed to enhance the system’s active control of the power supply level and optimize its process. Its effectiveness is proved by the results of simulation models, which demonstrated tremendous drops in Total Harmonic Distortion (THD), more significant power factors, and better system voltage stability. The instance of charging EVs has significantly posed stability challenges to which the AI filter can highly respond. The results illustrate the potential of AI-powered active filters to provide higher reliabilities of the electric vehicle infrastructure while being responsive to the flexible grid connection, which increased adoption of EVs entails. Keywords: Electric Vehicles, Power Quality, Series Active Filters, Artificial Intelligence, Harmonic Mitigation, Power Factor, Voltage Stability, AI-Controlled Filters, EV Charging Stations, Grid Integration